The effect of BaTiO3 particle shape on complex permittivity of 0.98MgTiO3–0.02BaTiO3 composite powders at GHz frequencies. (April 2016) - Tuhkala, M.; Maček, M.; Siponkoski, T.; Juuti, J.; Teirikangas, M.; Suvorov, D.; Jantunen, H.
Graphical abstract: Highlights: Elongated micrometre sized BaTiO3 particles had strong effect on permittivity. Effect was significantly stronger compared to μm and nm sized spherical particles. Properties could be tailored by varying the particle shapes of dielectric powders. Could be utilized, e.g., in a production of electrical composites for RF applications. Abstract: The effect of BaTiO3 particle shape on the properties of 0.98MgTiO3 –0.02BaTiO3 composite powders was characterized and analyzed using an indirectly coupled open-ended coaxial cavity resonator at gigahertz frequencies. Elongated micrometre sized BaTiO3 particles were found to have a significantly stronger effect on permittivity when compared to composite powders having micro and nano sized spherical BaTiO3 particles. Inclusion permittivities and dielectric loss tangents of composite powders increased from that of pure MgTiO3 powder, 13.3 and 4.6 × 10 −3, up to 15.7 and 1.7 × 10 −2 with needle shaped BaTiO3 particles, respectively. The presented results give valuable information for tailoring the properties of dielectrics which can be utilized in the vast field of electronic component manufacturing.